Review and reflections of legislation and policies on shipping decarbonization under China’s “dual carbon” target - Yang, Weiming; Chen, Xidi; Liu, Yu (Frontiers in Marine Science, 2023)
Although shipping is a relatively energy-saving and environmentally friendly mode of transportation, the growth rate of its energy consumption and carbon emissions far exceeds that of other industries. As an important response to climate change, shipping decarbonization is not only an important part of achieving the temperature control goal of the Paris Agreement but is also an important direction for the future development of China’s ecological civilization construction. China has formulated and promulgated legislation and policies on shipping decarbonization both at the national and local levels. The proposal in 2020 of the goal of carbon peaking and carbon neutrality has accelerated this process. In this context, this paper aims at reflecting on legislation and policies for decarbonization of shipping under China’s “double carbon” target, and proposing suggestions for improvement. Firstly, we systematically review China’s legislation and policies on shipping decarbonization to outline the normative system of China’s shipping carbon reduction. Secondly, this paper evaluates China’s legislation and policies on shipping decarbonization from the perspective of both achievements and challenges. Finally, this paper proposes that China’s legislation and policies for decarbonization of shipping should be further improved from two aspects: enhancing mandatory force and expanding normative content.